Representación del erotismo en la novela Del amor y otros demonios de Gabriel García Márquez - Azogue Gomez, Yessenia Sabrina (2025)
The general objective of this research was to analyze the representation of eroticism in the novel "Del amor y otros demonios" by Gabriel García Márquez. This analysis focuses on how eroticism is manifested in colonial society, by constructing a main theme to understand the narrative of the work. The methodology used responds to a qualitative approach, based on a descriptive and documentary study. The corpus analyzed is constituted by the aforementioned novelistic work. For the analysis and interpretation of the data, the hermeneutic method was used, while for the analysis techniques, literary analysis cards were designed and applied in order to fulfill the established objectives and argue the interpretations. The results of the research show that the representation of eroticism in the novel not only explores human desires, but also functions as a critique of the social and religious norms of the colonial era. By situating eroticism as an act of transgression against imposed taboos, Gabriel García Márquez highlights how power structures attempt to control human behavior. In this way, the novel reveals how these oppressive actions perpetuate inequalities and contradictions, leading the characters to seek their liberation